2016
DOI: 10.2134/agronj2016.06.0329
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant and Polymer‐Coated Sand Effects on Deficit Irrigated Bermudagrass Turf

Abstract: Sand topdressing and soil surfactants are commonly applied to turfgrass areas but it is unclear whether these practices improve visual appearance or reduce hydrophobicity under defi cit irrigation. A study was conducted from 2011 to 2013 at New Mexico State University in Las Cruces, NM, to evaluate two topdressing materials and a soil surfactant on defi cit irrigated Princess 77 bermudagrass (Cynodon dactylon L.) grown on a loamy sand (mixed, thermic Typic Torripsamment). Treatments consisted of monthly applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…The previously mentioned study by Alvarez et al (2016) included monthly applications of hydrophilic sand, topdressing sand alone, or combinations of liquid surfactants and topdressing sands with irrigation replacing 50 or 70% of ET 0 . The current study only evaluated a single application early in the growing season where hydrophilic sands were mixed with topdressing sand at application.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previously mentioned study by Alvarez et al (2016) included monthly applications of hydrophilic sand, topdressing sand alone, or combinations of liquid surfactants and topdressing sands with irrigation replacing 50 or 70% of ET 0 . The current study only evaluated a single application early in the growing season where hydrophilic sands were mixed with topdressing sand at application.…”
Section: Resultsmentioning
confidence: 99%
“…Surfactants can decrease soil hydrophobicity by breaking the surface tension between soil particles and have been especially effective in sandy soils where decomposition and root exudates coat soil particles with hydrophobic lipid compounds (Alvarez et al, 2016; Cisar et al, 2000; Leinauer et al, 2007). Golf course superintendents and other professional turfgrass managers regularly apply surfactants as part of their routine turfgrass management (Alvarez et al, 2016). Studies have demonstrated the ability of surfactants to improve water use efficiency and conservation as part of standard turfgrass management programs (Alvarez et al, 2016; Cisar et al, 2000; Leinauer and Devitt, 2013).…”
Section: Useful Conversionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported either an increase (Soldat et al, 2010) or no effect (Schiavon et al, 2014) in SWC after APG application. Leinauer et al (2001) and Alvarez et al (2016) reported that the effectiveness of a surfactant in increasing SWC can vary depending on the application rate and weather conditions. The general decline in SWC from Tuesdays to Mondays under both irrigation regimes (Figure 5), is logical since irrigation was applied on Tuesdays only under the ONCE irrigation regime and on Tuesdays and Thursdays under the SPLIT irrigation regime, with no water being applied on Mondays.…”
Section: Soil Water Contentmentioning
confidence: 99%